ADVANCED NANOCARRIERS FOR CONTROLLED DRUG AND GENE DELIVERY IN CHRONIC DISEASES - Ren Suzuki; Daiki Nishida; Nila Trisna Yulianti (Journal of Biomedical and Techno Nanomaterials, 2026)
Chronic diseases such as cancer, cardiovascular diseases, and neurodegenerative disorders pose significant treatment challenges due to their complexity and resistance to conventional therapies. Nanocarriers, as advanced drug and gene delivery systems, offer a promising solution to address these challenges by providing controlled release, improved targeting, and enhanced therapeutic efficacy. The ability to design nanocarriers that are biocompatible, stable, and capable of precise targeting to diseased tissues holds potential for revolutionizing the treatment of chronic diseases. This study aims to explore the design, development, and evaluation of advanced nanocarriers for controlled drug and gene delivery in chronic diseases. The research focuses on evaluating the efficacy of various nanocarriers, including liposomes, dendrimers, and nanoparticles, in improving drug bioavailability, targeting precision, and therapeutic outcomes in chronic disease models. The research utilizes in vitro cell culture studies and in vivo animal models to assess the effectiveness of different nanocarriers. Characterization techniques, including dynamic light scattering (DLS), transmission electron microscopy (TEM), and drug release assays, are used to evaluate the properties and performance of the nanocarriers. The study demonstrates that advanced nanocarriers significantly improve drug delivery efficiency, reduce systemic toxicity, and enhance therapeutic outcomes in chronic disease models. Gene delivery using nanocarriers also shows promising results in terms of targeted therapy. Advanced nanocarriers are a promising tool for controlled drug and gene delivery, offering potential breakthroughs in the treatment of chronic diseases by improving precision and minimizing side effects.